Analisis Kemampuan Pemahaman Konsep Siswa pada Materi Operasi Bilangan Bulat - Choirunisa, Choirunisa; Fawensi, Puja Teressa; Utari, Rahma Siska; Kurniadi, Elika; Yukans, Septy Sari (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2024)
Understanding the concept of whole number operations, especially addition and subtraction, is an important basis in mathematics that must be mastered by students. However, many students still experience difficulties in understanding the material, especially in more complex operations. This study aims to analyze students' concept understanding ability on whole number operation material by applying the demonstration method. The research method used was descriptive qualitative, involving 26 students of class VII.A at Srijaya Negara Junior High School Palembang as research subjects. Data was collected through written tests consisting of five description questions and interviews to explore students' understanding more deeply. The results showed that 47.62% of students scored in the high category, 14.28% in the medium category, and 38.09% in the low category, with an average score of 59.05 which indicates understanding in the medium category. The application of the demonstration method, in which students actively participated by walking on the marked tiles, proved to increase students' enthusiasm and provide a more memorable learning experience. Nonetheless, the proportion of students in the low category indicates the need for more attention in the learning process. This study concludes that the demonstration method is effective in improving concept understanding, but needs to be balanced with additional approaches to support students who have difficulty in understanding integer operation material.